Identifying resilience-promoting factors for refugee survivors of torture - Phyu Pannu; Burt, Keith; Fondacaro, Karen (Torture Journal, 2022)
Introduction: There are 1.3 million refugee survivors of torture currently living in the United States today. While a substantial body of research has been growing on refugee mental health, few studies have focused on refugee resilience. Objective: The current study focuses on a clinical sample of refugee survivors of torture to examine resilience-promoting factors, including community engagement, employment, English fluency, and psychological flexibility. Specifically, our study conducted moderation and mediation analyses to better understand how these resilience-promoting factors impact the torture-mental health relationship. Results: Findings showed that torture severity was significantly and positively associated with all mental health symptoms, and psychological flexibility was significantly and negatively associated with all mental health symptoms, including PTSD, depression, and anxiety. Psychological flexibility also emerged as a significant mediator of the torture-mental health relationship, such that individuals with a history of greater torture severity reported higher mental health symptoms via lower psychological flexibility. Additionally, English fluency and employment, but not community engagement, showed significant negative correlations with mental health symptoms. However, resilience-promoting factors did not interact with torture severity to predict mental health symptoms. Conclusion: The findings from this study identified variables that may have a meaningful impact on the mental health of refugee survivors of torture and provide insights and implications in treating this population from resilience-oriented clinical frameworks.